Atypical Presentation of Congenital Triangular Alopecia: A Case Series in Italy - Starace, Michela; Carpanese, Miriam Anna; Abbenante, Diego; Bruni, Francesca; Piraccini, Bianca Maria; Alessandrini, Aurora (Dermatology Practical & Conceptual, 2020)
Background: Congenital triangular alopecia (CTA) is a benign, asymptomatic, nonprogressive, localized and noncicatricial type of alopecia that is usually first noted during infancy or childhood. The pattern of hair loss is traditionally described as triangular, oval or lancet shaped with apex toward the vertex.Objectives: We present a case series of CTA located in unusual sites.Patients and Methods: We performed trichoscopy in 78 patients with CTA. From this group, we selected 10 individuals (4 males and 6 females) whose disease was not localized on the typical scalp area.Results: The alopecic area was located on the occipital region in 5 patients, the parietal region in 4 patients, at the vertex in 1. With trichoscopy, vellus hairs were detected in all patients, and evidence of empty follicles was noticed only in 3 patients.Conclusions: In contrast with the preconceived notion that all CTAs are frontotemporal, our case series points out that this disease could be localized in other scalp sites.